CONTEMPORARY STATE POLICY FOR THE DEVELOPMENT OF DIGITAL LITERACY OF PUBLIC SERVANTS AND CITIZENS OF UKRAINE - Zhyliaiev , Ihor; Semenchenko , Andrii (Theory and Practice of Public Administration, 2020)
Formed to a sovereign policy of development of digital literacy of public services and those of the population. The current status of the main trends of digital transformations in Ukraine, the international and national progress in Ukraine, the security of the Ukrainian-Swiss programs “E-governance for the sake of transparency of government and citizen participation) (EGAP) are secured. Propositions include a system of basic principles, meta, etapi, strategic goals, results, clear ideas, basic forms of precedence, approaches to the target list of priority contingents, marked main factors of awareness, realism of reality. The aim was to increase the widespread understanding in the framework of the EGAP program for the development of a proprietary conceptual concept and the development of digital skills of public service and community members. It is invoked for successful realization of the intended assignment of consolidation of all the institute of huge suspension, for the front of the Ministry of Economy, the NADS, the Ministry of Education and Science, the Ministry of Social Affairs, the massive government. The recommendations are formulated to the authorities to formulate and implement effective public policies and administer with the development of digital skills. The necessity of development of the state target program of training of CSs of different categories of citizens and DS is considered, taking into account their peculiarities and gained national and international experience in this sphere, combining resources and efforts of public authorities, business, public organizations and international technical assistance. It is proposed to develop methods for assessing the level of digital skills of public officials and to include digital competencies in the qualification requirements for the professional knowledge and skills of public servants needed to fulfill their job responsibilities, with the identification of basic, intermediate and special levels of qualification. Develop appropriate training programs for each group.